PROBLEM-BASED LEARNING: AN OVERVIEW OF ITS PROCESS AND IMPACT ON LEARNING - Amir, Sohail; Mehboob, Usman; Sethi, Ahsan; Jamil, Brekhna (Pakistan Journal of Physiology, 2022)
Problem-based learning (PBL) has a long history of advocating experience-based education. Psychological research and theory suggest that by having students learn through the experience of solving problems, they can learn both content and thinking strategies. Problem-based learning (PBL) is an instructional strategy that allows students to seek solutions to unstructured, real-world situations. PBL focuses student learning on a complicated topic with no one proper answer. Students collaborate in groups to determine what they need to know in order to solve an issue. Rather than imparting knowledge, the teacher’s role is to aid the learning process. PBL aims to help students build flexible knowledge, effective problem-solving abilities, SDL skills, effective collaboration skills, and intrinsic motivation. The process of PBL includes identification of outcome, designing a scenario, introduction of PBL, research, performance and assessment. When compared to students in a lecture-based learning environment, studies on the effectiveness of PBL tend to be mixed, but they all suggest that students who have experienced PBL acquire similar or less learning gains when it comes to short-term information acquisition. However, in terms of long-term information retention, the results strongly favour PBL. Pak J Physiol 2022;18(1):